Assessing the Effect of Super Plasticizer on Scoria Concrete. - Turyasiima, Ronald (Kabale University, 2023)
The objective of this research was to investigate the feasibility and effectiveness of the use of scoria, in lightweight concretes. Coarse scoria of 5/10 and 10/20 mm were used. A portion of the aggregate mixtures had an average particle size B100 l m. Scoria are often used as the constituents of structural concrete and insulating materials. The usability of the concretes tested in this study broadens as the porosity of the mixtures decreased and the cement dosage increased. According to the cement dosage and frequency types, the absorption coefficients of concretes ranged from 0.14 to 0.47. A compressive strength of 19 MPa corresponded to a density of 1800 kg/m3; compressive strengths from 10 to 18 MPa mapped to densities ranging from 1300 to 1700 kg/m3. The thermal conductivity of mixed concretes without scoria reached a maximum value of 0.268 W/m K. The thermal conductivity values of the concretes mixed without sand were below 0.403 W/m K. As sand content increased, the conductivity evolved from 0.565 to 0.657 W/m K. Freeze–thaw stability tests were conducted for 400 cycles or until specimens deteriorated.